2020
DOI: 10.1371/journal.pone.0235205
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of pharmacy professionals on generic medicines in Eastern Ethiopia: A cross-sectional study

Abstract: Background Generic medicines are similar to innovator medicine in terms of safety, quality, efficacy, dosage form, strength, and route of administration. They have the same therapeutic use to innovator medicines and available at a far lower price. However, health professionals' poor knowledge and attitude may limit its utilization. The present study aimed at assessing the knowledge, attitude, and practice of pharmacy professionals towards generic medicines in Harar city, Eastern Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
6
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 28 publications
7
22
6
10
Order By: Relevance
“…In this study, ~65% of the students agreed that generic products are similar in efficacy, quality, and safety compared to the original branded products. These findings were in line with earlier studies from Ethiopia (67%) ( 20 ), but higher than the findings of James et al (55%) ( 21 ), Belay et al (52.9%) ( 22 ), Toklu et al (46.1%) ( 23 ), and Al Hussain et al (42.2%) ( 24 ). However, our results were still lower than earlier studies by Grover et al (70%) and Wajid et al (72.2%) among community pharmacists ( 3 , 25 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, ~65% of the students agreed that generic products are similar in efficacy, quality, and safety compared to the original branded products. These findings were in line with earlier studies from Ethiopia (67%) ( 20 ), but higher than the findings of James et al (55%) ( 21 ), Belay et al (52.9%) ( 22 ), Toklu et al (46.1%) ( 23 ), and Al Hussain et al (42.2%) ( 24 ). However, our results were still lower than earlier studies by Grover et al (70%) and Wajid et al (72.2%) among community pharmacists ( 3 , 25 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, ∼65% of the students agreed that generic products are similar in efficacy, quality, and safety compared to the original branded products. These findings were in line with earlier studies from Ethiopia (67%) (20) (3,25). One study among Yemeni pharmacy students from private universities revealed that students perceived generic medicines to be inferior and less effective and, thus, could lead to more side effects compared with branded medicines (14).…”
Section: Discussionsupporting
confidence: 91%
“…Pharmacists play an important role in providing direct patient care by promising the rational use of medicine and promoting cost-effective generic medication use. 1 Pharmacists also play a role in prescribing and delivering pharmaceutical care services, due to which they are involved in patient care. Since pharmacists are considered well-versed with drugs, they are experts in resolving, recognizing, and preventing drug-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…To meet drug demand and reduce budgetary expenditure on drugs, the marketing of generic medicines is a viable alternative that is 20% to 90% less expensive than the brand-name counterpart. 3,4 The pharmacist is critical for generic medicine promotion because they are directly involved in the formulation and dispensing of the medication. Pharmacists' clinical activities have advanced significantly over the last decade to ensure the appropriate and economical use of medications.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists' clinical activities have advanced significantly over the last decade to ensure the appropriate and economical use of medications. 4 However, successful generic medicine utilization is only achievable when pharmacists receive proper training in generic drugs as part of their degrees. In India, a variety of pharmacy degrees are available, including the Diploma in Pharmacy (D.Pharm), the Bachelor of Pharmacy (B.Pharm), the Master of Pharmacy (M.Pharm), the Master of Science in Pharmacy [MS (Pharm)], and the Master of Technology in Pharmacy [MTech (Pharm)], as well as the Doctor of Pharmacy (Pharm.D) and doctor of philosophy in pharmacy (PhD).…”
Section: Introductionmentioning
confidence: 99%